SYNTHESIS AND FUNCTIONALIZATION OF CARBON DOTS HAVING ABSORBANCE AT THE FIRST NIR WINDOW BY AMINO AND CARBONYL FUNCTIONAL GROUPS - Sinda Santika, Arum
Carbon dots (CDs) are nanoparticles with a size below 10 nm with good photoluminescence properties. CDs material has superior properties such as high biocompatibility, non-toxicity, high water solubility, good photoluminescence and multicolor, photostability, and easy synthesis. This makes CDs possible to be applied in energy conversion, optoelectronic devices, and biomedicine. CDs are considered the best candidates for photothermal and bioimaging agents in cancer therapy processes in the biomedical field. CDs that can be applied as photothermal agents can absorb the light range of the first NIR window (650-900 nm). Various synthesis or functionalization methods can obtain absorbance properties in the first NIR window region on CDs. Our previous research has reported that various nitrogen and oxygen functional groups on CDs can regulate the absorbance properties of CDs up to the range of the first NIR window. However, further investigations regarding optimizing the ratio of oxygen and nitrogen functional groups and the optical transition mechanism involved have not been further evaluated. Therefore, this study synthesized CDs and functionalized them in-situ using the hydrothermal method with citric acid and urea as the primary ingredients. These basic materials were selected to functionalize the surface of the CDs formed by amino and carbonyl groups so that the resulting CDs had an absorption peak in the first NIR window region. This research begins with a computational study of CDs material using Time-Dependent Density Functional Theory (TD-DFT) to find the optimum ratio of amino and carbonyl functional groups that produce absorbance properties in the first NIR window region with the highest intensity. Furthermore, this TD-DFT study was also conducted to study the role of the amino and carbonyl functional groups and their interactions with the optical and electronic properties of the CDs structure. The results of the TD-DFT study show that the combination of amino and carbonyl with an amino to carbonyl concentration ratio from 1:2 to 4:2 can shift the absorbance peak to a longer wavelength as far as 171 nm. The value of this shift is much larger than that of CDs, which are only functionalized by one type of functional group, amino group, or carbonyl group, with shift values as far as 120 nm and 84 nm. Furthermore, the TD-DFT study also revealed the interaction mechanism between the amino and carbonyl groups to the optical and electronic properties of CDs, where there is a synergistic effect between the amino and carbonyl groups which results in a shift in the absorbance peak and strengthens the absorption intensity in the first NIR window region. In addition, the band gap energy of the amino CDs carbonyl can be regulated by optimizing the amino to carbonyl ratio on the CDs' surface. Computational study results show that amino and carbonyl synergistically can efficiently regulate CDs' optical and electronic properties through Frontier Orbital Hybridization and high charge transfer. This is also supported by experimental results, where the absorption peak of amino CDs carbonyl, which has been synthesized at various amino and carbonyl ratios through hydrothermal heating, experiences a red shift as an amino to carbonyl concentration increases. The peak of the amino CDs carbonyl absorbance showed a significant red-shift from 550 nm to 650 nm as the amino to carbonyl ratio increased from 2:1 to 3:1. Experimental investigation results which are in line with computational results indicate that the combination of amino and carbonyl groups is synergistically able to regulate the peak absorbance of CDs material. Thus, this study can provide new scientific insight into strategies for adjusting CDs' optical and electronic properties to suit application requirements.